Experimental Investigation of Free Space Optical Channel Performance in the Arctic Weather - Sahil Nazir Pottoo; Pal Gunnar Ellingsen; Tu Dac Ho (IEEE Access)
This paper investigates the technical aspects of the 1550 nm free space optical (FSO) link in extreme Arctic weather, specifically in falling snow, which is currently understudied. We measured the time variation of the received optical power in many snowfall events and derived attenuation statistics. Continuous measurements allowed us to estimate attenuation under varying temperatures and humidity to examine the after-snow channel impairments. Our results show several shortcomings in the International Telecommunication Union-Radio Communication (ITU-R) snow attenuation model and verify that a correlation exists between snow features, snowfall rate, temperature, and humidity in determining the total snow attenuation. We demonstrated the relationship between snow properties, temperature, humidity, and attenuation under both in-snow and post-snow environments. Furthermore, based on the experimental results, we recommend several mitigation techniques to realize FSO communication during challenging Arctic weather conditions. Lastly, we present a feasibility study of FSO in Svalbard at 78°N latitude.